2015
DOI: 10.2514/1.j053277
|View full text |Cite
|
Sign up to set email alerts
|

Combining Shaping and Flow Control for Aerodynamic Optimization

Abstract: Shape optimization and flow control have been extensively studied in the past to improve the performance of wings and blades. However, they are commonly applied as two separate disciplines, with their interactions being rarely studied. The present work aims to examine and identify the potential to explore the interactions between the two disciplines and is chiefly concerned about two related issues: 1) how much more performance improvement can be obtained by combining the shape optimization with the flow contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The strong coolant-base flow interaction in the tip region would suggest that cooling injection can be to some extent considered as a means of flow control. It has been shown that combining flow control and geometry shaping would provide extra performance gain than either shaping or flow control respectively (Zhang and He, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The strong coolant-base flow interaction in the tip region would suggest that cooling injection can be to some extent considered as a means of flow control. It has been shown that combining flow control and geometry shaping would provide extra performance gain than either shaping or flow control respectively (Zhang and He, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The RSM has been applied to aerodynamic optimization studies and data fitting to reduce errors in the data acquired in flight conditions [24][25][26][27][28][29]. Rosenbaum et al [24] and Sevant et al [25] applied the RSM to design the wing geometry of aircraft.…”
Section: Introductionmentioning
confidence: 99%
“…Rosenbaum et al [24] and Sevant et al [25] applied the RSM to design the wing geometry of aircraft. Zhang et al [26] applied the RSM to a coupling problem between the shape optimization and flow control in order to improve the performance of the wings and blades. Papila et al [27] applied the RSM to reduce both noise and modeling errors for designing a high-speed civil transport wing structure, and successfully demonstrated reduced error inherent in the modeling and optimizing the wing geometry and structure [27].…”
Section: Introductionmentioning
confidence: 99%